If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying m^{2}+ -5m = 0 Reorder the terms: -5m + m^{2}= 0 Solving -5m + m^{2}= 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), 'm'. m(-5 + m) = 0## Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0## Subproblem 2

Set the factor '(-5 + m)' equal to zero and attempt to solve: Simplifying -5 + m = 0 Solving -5 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + m = 0 + 5 Combine like terms: -5 + 5 = 0 0 + m = 0 + 5 m = 0 + 5 Combine like terms: 0 + 5 = 5 m = 5 Simplifying m = 5## Solution

m = {0, 5}

| 5x^2=50 | | t^2+7t-35=2t-11 | | 2(x^2)-7x=1 | | x^2+4x-2m=0 | | 27x^2-5x=0 | | 7e^8+t=2 | | 13x^2-28x=0 | | 15n+3n^4-4n+12n^4+n= | | 2x^2-24x=-2x^2-7x-18 | | 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions